The Puzzle of Unemployment and Inflation: A Causality Analysis to Ethiopia - Minyahil Alemu Haile (Journal of International Trade, Logistics and Law, 2020)
The puzzle of unemployment and inflation has remained controversial. The choice between the two ends up with cost borne from the other end. Of course, the policy aim is to keep them both to their minimum possible rates. Countries need to examine the dynamics between the two and choose one with lesser harm to the general system. We applied Granger Causality approach to examine the nature of causality between inflation and unemployment to Ethiopia, using a time series running from 1984 to 2018. Accordingly, the-two-way causality between inflation and unemployment (cyclical) variables has been confirmed. Thus, macroeconomic policies need to appreciate this interdependence while designing policy settings.